Effects of high-intensity and blood flow-restricted low-intensity resistance training on carotid arterial compliance: role of blood pressure during training sessions - Ozaki, H.; Yasuda, T.; Ogasawara, R.; Sakamaki-Sunaga, M.; Naito, H.; Abe, T. (European Journal of Applied Physiology, 2013)
We examined the effects of high-intensity resistance training (HIT) and low-intensity blood flow-restricted (LI-BFR) resistance training on carotid arterial compliance. Nineteen young men were randomly divided into HIT (n = 9) or LI-BFR (n = 10) groups. The HIT and LI-BFR groups performed 75 and 30 %, respectively, of one-repetition maximum (1-RM) bench press exercise, 3 days per week for 6 weeks. During the training sessions, the LI-BFR group wore elastic cuffs around the most proximal region of both arms. Muscle cross-sectional area (CSA), 1-RM strength, and carotid arterial compliance were measured before and 3 days after the final training session. Acute changes in systolic arterial pressure (SAP), plasma endothelin-1 (ET-1), nitrite/nitrate (NOx), and noradrenalin concentrations were also measured during and after a bout of training session. The training led to significant increases (P < 0.01) in bench press 1-RM and arm and chest muscle CSA in the two training groups. Carotid arterial compliance decreased significantly (P < 0.05) in the HIT group, but not in the LI-BFR group. There was a significant correlation (r = -0.533, P < 0.05) between the change in carotid arterial compliance and the acute change in SAP during training sessions; however, ET-1 and NOx did not correlate with carotid arterial compliance. Our results suggest that muscle CSA and strength increased following 6 weeks of both HIT and LI-BFR training. However, carotid arterial compliance decreased in only the HIT group, and the changes were correlated with SAP elevations during exercise sessions.